2017
DOI: 10.37358/rc.17.5.5593
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Femoral Head Osteonecrosis

Abstract: In recent years, there has been an increase in the number of studies on the etiology of femoral head necrosis. We retrospectively reviewed all patients diagnosed with aseptic necrosis of the femoral in the period of 2010-2015. We recorded a total of 230 cases diagnosed with aseptic necrosis of the femoral head, group was composed of 65.7% men and 34.3% women, risk factors identified was 19.13% (post-traumatic), 13.91% (glucocorticoids), 26.52% (alcohol), 3.47% (another cause) and in 36 95% of the cases no risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Numerous studies have been conducted in recent years to investigate the etiology of AVN, in which a review study that has examined several studies has identified steroid and alcohol use as the most important risk factors. [ 16 ] Studies have also reported the use of corticosteroids as the main risk factor for AVN. In a study conducted at Rasoul Akram Hospital in Tehran, Iran, in 2013–2015, 42% of patients with AVN were treated with corticosteroids, 4% with bisphosphonates, and 4% with hematologic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted in recent years to investigate the etiology of AVN, in which a review study that has examined several studies has identified steroid and alcohol use as the most important risk factors. [ 16 ] Studies have also reported the use of corticosteroids as the main risk factor for AVN. In a study conducted at Rasoul Akram Hospital in Tehran, Iran, in 2013–2015, 42% of patients with AVN were treated with corticosteroids, 4% with bisphosphonates, and 4% with hematologic disease.…”
Section: Discussionmentioning
confidence: 99%